PsycEXTRA Dataset 1998
DOI: 10.1037/e382712004-001
|View full text |Cite
|
Sign up to set email alerts
|

Instructional Policy and Classroom Performance: The Mathematics Reform in California

Abstract: Educational reformers increasingly seek to manipulate policies regarding assessment, curriculum, and professional development in order to improve instruction. They assume that manipulating these elements of instructional policy will change teachers' practice, which will then improve student performance. We formalize these ideas into a rudimentary model of the relations among instructional policy, teaching, and learning. We propose that successful instructional policies are themselves instructional in nature: b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
155
1
6

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(168 citation statements)
references
References 5 publications
6
155
1
6
Order By: Relevance
“…The SSIs used professional development to enhance teacher content knowledge and the use of standards-based instruction, a decision supported by research indicating that improved teacher content knowledge may change teaching practice (Cohen & Hill, 1998;Kahle, 1997). For example, when teachers cover topics about which they are well-prepared, they encourage student questions and discussions, spend less time on unrelated topics, permit discussions to move in new directions based on student interest, and generally present topics in a more coherent wayÐall strategies included as standards-based teaching (Kahle & Rennie, 1993;Leder, 1990;NSF, 1998).…”
Section: Urban Education In Science and Mathematicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SSIs used professional development to enhance teacher content knowledge and the use of standards-based instruction, a decision supported by research indicating that improved teacher content knowledge may change teaching practice (Cohen & Hill, 1998;Kahle, 1997). For example, when teachers cover topics about which they are well-prepared, they encourage student questions and discussions, spend less time on unrelated topics, permit discussions to move in new directions based on student interest, and generally present topics in a more coherent wayÐall strategies included as standards-based teaching (Kahle & Rennie, 1993;Leder, 1990;NSF, 1998).…”
Section: Urban Education In Science and Mathematicsmentioning
confidence: 99%
“…Other studies provide evidence that professional development experiences that enhance teachers' subject matter knowledge and expand their range of teaching practices are likely to enhance student achievement (Chaney, 1995;Cohen & Hill, 1998;Damnjanovic, 1998;Kahle, 1997;Monk, 1994). For example, Monk (1994) has found that additional coursework in speci®c areas (e.g., number and kinds of science and mathematics courses) has a positive effect on student learning, while additional coursework by teachers in unrelated subjects has no, or a negative, effect on student learning.…”
Section: Urban Education In Science and Mathematicsmentioning
confidence: 99%
“…Studies revealed that student achievement is correlated to teachers' continued learning activities (Cohen & Hill 1997, Wiley & Yoon 1995, Brown et al 1995. Teacher confidence, too, has been regarded by the International Association for the Evaluation of Educational Achievement (Schmidt & Cogan 1996) as being essential in qualifying teacher competence.…”
Section: Introductionmentioning
confidence: 99%
“…Collaboration between schools and universities has been advocated as an approach for improving the practices of teachers and students' learning (Cohen & Hill, 2000;Ramsey, 2000). While the goals and practices of university-school partnerships vary, there exists a shared belief that collaboration creates learning opportunities that are richer than either institutio could provide alone and ensure a focus on both theoretical as well as practical issues (Rice, 2002).…”
Section: Collaborative Inquiry To Support Teacher Professional Learningmentioning
confidence: 99%